Di-μ-chlorido-bis[dichlorido(N,N-diethylacetamidinato)(N,N-diethylacetamidine)titanium(IV)] acetonitrile disolvate - Straessler, Nicholas A. (International Union of Crystallography, 2007)
In the centrosymmetric title compound [Ti(2)Cl(6)(C(6)H(13)N(2))(2)(C(6)H(14)N(2))(2)]·2C(2)H(3)N, an inversion center relates the two Ti atoms which display a distorted octahedral coordination geometry. There are two uncoordinated acetonitrile solvent molecules per molecule of title compound in the crystal structure.